Distribusi Spasial dan Temporal Kepiting Kelapa (Birgus latro Linn 1767) di Daeo Kabupaten Pulau Morotai, Maluku Utara - Rugaya Serosero; . Sulistiono; Nurlisa Alias Butet; Etty Riani (Institut Pertanian Bogor, 2018)
This study aims to describe the size distribution of coconut crabs spatially and temporally in Daeo, Morotai Island, North Maluku. The captching was carried out at three stations, namely in areas adjacent to residential areas (station I), steep terrain with varying vegetation (station II), and shallow areas with various vegetation and coconut trees (station III). The collections of samples were conducted using coconut bait and catching directly by hand. Their lengths of cephalotorax plus rostrum (Cp+r) and thorax (TL) and weight were measured. The habitat conditions of natural vegetation were also observed. Data collected in catch (spatial) were analyzed with non-parametric Mann- Whitney (α0.05) and temporal tests with Kruskal Wallis test (α0.05). The results showed that the total numbers of catched coconut crabs were 581 individuals consisted of 314 and 267 males and femalescoconut crabs). The weight ranges of male and female coconut crabs were 50-990 and 50-520 grams, respectively. The ranges of Cp+r on male and female coconut crabs were 43.98-114.72 mm and 43.98-90.67 mm, respectively. The sizes of the TL in male and female coconut crabs were 19.56-54.86 mm and 19.56-48.65 mm, respectively. Non-parametric Mann-Whitney test of the number of spatial coconut crab catched in station I was different from those in station II and stasion III (P<0.05). The numbers coconut crabs catched were not temporally different (P>0.05). The spatial environmental qualities were not different (P>0.05) and the temporal parameters were significantly different (P<0.05) except pH that was not significantly different (P>0.05). Station III had denser vegetation than stations I and II.